THE HARMONIZATION OF TRADITIONAL AND MODERN INSTRUMENTAL PERFORMANCE PRACTICES - Qo‘ziyev Toyir Asqarovich (Modern American Journals, 2026)
This article examines the interaction and harmonization of traditional and modern instrumental performance practices within the continuous development of musical art. The study analyzes the pedagogical, aesthetic, and artistic foundations of traditional performance based on oral transmission and the master–apprentice system, alongside modern performance approaches shaped by notation, technology, and academic music education. Particular attention is paid to the importance of balancing tradition and innovation in preserving and developing national musical heritage. The article argues that the integration of traditional and modern performance practices ensures the sustainable development of national music and enhances its artistic and aesthetic value.
Keywords: Instrumental performance, traditional performance, modern performance, master–apprentice system, national musical heritage, musical thinking.